Analisis dan Perancangan Sistem eCRM pada PT Paramitra Media Perkasa - Siswono Siswono; Juni Liem; Arieany Prasetyo (Bina Nusantara University, 2005)
Customers are the key to achieve company’s success, that’s why company should actively participate in keeping a good relationship with them. One of the ways to create a good relationship with customers is by applying e-CRM (Customer Relationship Management). A research at PT Paramitra Media Perkasa is focused in marketing by interviewing managers and telemarketers, analizying business process, and after doing library research. Based on the analysis,it can be figured out a problem in continuously making a relationship with customers. With e-CRM system, hopefully it will help company manage and keep a good relationship with costumers, as a result it will able to increase profit and company’s productivity.Keywords: